Penerapan Model Sinektik Untuk Meningkatkan Kemampuan Menulis Cerpen Bagi Mahasiswa - Ahsin, Muhammad Noor; Ristiyani, Ristiyani (Universitas Muria Kudus, 2019)
Writing skills are skills that students of the Indonesian Language and Literature Education (PBSI) study program need to have. In studying Literature Expression Writing courses in the PBSI Study Program at Muria Kudus University, students are expected to be able to write literary works, for example writing short stories. The problem is, writing short stories is still considered to be a difficult thing. Students still feel heavy and have difficulty writing short stories. This study aims at first explaining the improvement of PBSI students' short story writing skills with a social synectic model with a multicultural context in the subject of literary expression. Second, explaining the attitude of students in learning to write short stories with a social synectic model with a multicultural context. The method used in this study used a class action research design which was carried out for two cycles. The process of collecting data is done through test techniques, in the form of assignments to write short stories. The results of research conducted showed evidence of increased skills in writing short stories in the first cycle of an average of 60.42%, while in the second cycle rose to 80.18%. Keywords: Writing, short stories, synectic models